Identification of a new methylation site in the Sept9 promoter region for the diagnosis of hepatocellular carcinoma - N. L. Lazarevich; P. M. Abramov; M. D. Fedorova; I. F. Kustova; D. A. Shavochkina; A. N. Katargin; N. P. Kisseljova; N. A. Dyakova; I. V. Botezatu; V. N. Kondratova; N. E. Kudashkin; Yu. I. Patyutko; et al. (Успехи молекулярной онкологии, 2019)
Background. Over 600,000 people die from hepatocellular carcinoma (HCC) each year worldwide. The disease is often detected at advanced stages and in many cases is not curable. Early diagnostic and monitoring of HCC recurrences remains a substantial problem in clinical oncology. That determines the need for a search for highly sensitive and specific biomarkers for the non-invasive of HCC diagnostics. The objective of the study. Identification of the hypermethylated locus in the promoter region of the septin 9 (Sept9) gene based on the annotated methylomes from the public databases. Experimental validation of methylation on a pilot panel of paired clinical samples of patients with HCC, as well as tissue samples from patients with benign liver tumors and lymphocytes from healthy donors. Materials and methods. To analyze the methyl data, samples of HCC from TCGA, hepatocellular adenoma from GEO (Gene Expression Omnibus) depository, peripheral blood cells and tissues of healthy donors from Methbank were used. Experimental validation of methylation levels of the identified site was carried out on a pilot panel of clinical samples by bisulphite pyrosequencing using PyroMark Q24.Results. Based on the analysis of methylome data, we selected cg20275528 site, which is characterized by high level of methylation in HCC tissues and minimal levels of methylation in non-tumor liver tissue, hepatocellular adenoma and peripheral blood of healthy donors. Experimental testing on a pilot panel of clinical specimens showed that the level of marker site methylation in HCC (42 % median) is significantly higher than in non-tumor liver tissues (3 % median) and benign neoplasms (1.5 % median) and exceeds the threshold value in HCC compared to paired samples of adjacent non-tumor liver tissue in 20 out of 30 studied cases (66.6 %). The general possibility for cg20275528 methylation detection in circulating DNA of plasma in HCC patients was shown.Conclusion. The obtained results indicate that the approach to the detection and experimental verification of diagnostically significant markers developed and tested in this study can be used to identify new differentially methylated sites and to establish new approaches for non-invasive HCC diagnosis.